Coping with neo-nomadic mobility: Frontex’s agent power in the EU’s extended borderland - Gruszczak, Artur (Review of European and Comparative Law, 2019)
Migration movements to Europe, triggered by dramatic political and social developments in North Africa and the Middle East, have contributed to a decrease in the level of security in the European Union and to the crisis of this organization. This article addresses the issue of migration in the context of the phenomenon of neo-nomadism and its effects on the policies of the member states of the European Union, as well as its institutions and agencies. The consequences of neo-nomadism are analyzed in regard to ​​the EU’s "extended borderland" on the example of the activities of the European Border and Coast Guard Agency (Frontex) in the Central Mediterranean. Frontex’s joint operations "Triton" and "Themis" serve as a useful frame of reference in examining this agency’s "agent power" expressed in activities concerning migratory movements in the EU’s "extended borderland". The hypothesis developed in this article holds that the dynamics of mobility resulting from the specific features of neo-nomadism activates the "agent power" of entities involved in mobility and border management in two forms: inclusionary, for humanitarian reasons, and exclusionary, for the sake of security. As an agency responsible for supporting the management of the EU’s external borders and implementing return policy, Frontex has concentrated its agent power on securing territory, borders and population at the expense of humanitarian search-and-rescue operations. Joint operations "Triton" and "Themis" have clearly highlighted the trend towards an exclusionary approach to migrants. Post-functionalism referring to the original conceptualisation put forward by Hooghe and Marx is the theoretical frame adopted in the present study. The research method is qualitative, based on desk research includng the analysis and interpretation of primary and secondary sources.